Bryophytes Harbor Cultivable Actinobacteria With Plant Growth Promoting Potential - Insuk, Chadabhorn; Kuncharoen, Nattakorn; Cheeptham, Naowarat; Tanasupawat, Somboon; Pathom-aree, Wasu (Frontiers in Microbiology, 2020)
This study was designed to investigate the cultivable actinobacteria associated with bryophytes and their plant growth promoting ability. Thirteen actinobacteria were isolated and tested for their ability to promote growth of plant in vitro and in planta. All isolates were able to produce IAA and siderophores. Six isolates were identified as members of the genus Micromonospora. Five isolates belonged to the genus Streptomyces and one each of Microbispora and Mycobacterium. Micromonospora sp. CMU55-4 was introduced to rare moss (Physcomitrium sphaericum (C. Ludw.) Fürnr and could increase the amount of carotenoid, fresh weight, and dry weight of this moss. In addition, this strain promoted capsule production, and rescued P. sphaericum’s gametophytes during acclimatization to land. Strain CMU55-4 was identified as Micromonospora chalcea based on whole genome sequence analysis. Its plant growth promoting potential was further characterised through genome mining. The draft genome size was 6.6 Mb (73% GC). The genome contained 5,933 coding sequences. Functional annotation predicted encoded genes essential for siderophore production, phosphate solubilization that enable bacteria to survive under nutrient limited environment. Glycine-betaine accumulation and trehalose biosynthesis also aid plants under drought stress. M. chalcea CMU55-4 also exhibited genes for various carbohydrate metabolic pathways indicating those for efficient utilization of carbohydrates inside plant cells. Additionally, predictive genes for heat shock proteins, cold shock proteins, and oxidative stress such as glutathione biosynthesis were identified.